Factors Affecting Customer Satisfaction of Last-Mile Delivery Logistics - Caberoy, Kim-J E.; Carsula, Carl Louise G.; Chua, Raymund Joseph L.; Tingson, Christine Gabrielle B.; Uy, Rofe Blaise B.; Valderama, Archimedes L. (American Journal of Management, 2025)
The study aims to determine the factors affecting customer satisfaction in last-mile delivery logistics, focusing on Delivery Riders’ Sense of Direction, Timeliness, Politeness, and Parcel Condition. It also covers satisfaction levels across select profiles. A descriptive research design was employed, using a researcher-made online questionnaire. A total of 385 participants were selected through purposive sampling. Data were analyzed using frequency, percentage, mean, and standard deviation. Findings revealed that participants were satisfied with all four factors. Delivery Riders’ Sense of Direction received the highest satisfaction rating, followed by Parcel Condition and Politeness, while Timeliness ranked lowest. Based on the results, the study concludes that these factors significantly influence overall customer satisfaction with last-mile delivery. The researchers recommend programs targeting the four key factors to enhance service quality. These initiatives aim to improve customer experience and satisfaction, helping delivery providers build a stronger competitive edge in the rapidly evolving last-mile delivery sector.